2015
DOI: 10.1007/s40495-015-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated Fatty Acids and Their Role in Cancer Chemoprevention

Abstract: Polyunsaturated fatty acids (PUFAs), including omega-3 (n-3) and omega-6 (n-6) PUFAs, are essential for human health. Recent research shows n-3 PUFAs and their mediators can inhibit inflammation, angiogenesis and cancer via multiple mechanisms, including reduced release of n-6 fatty acid arachidonic acid from cell membranes, inhibition of enzymatic activities, and direct competition with arachidonic acid for enzymatic conversions. In this review, we discuss inflammation-related cancer, anti-inflammatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 123 publications
1
48
0
2
Order By: Relevance
“…Studying of nutraceuticals has increased in last decades due to the significant expansion of cancer all around the world. According to the literature, some of the most important anti-cancer agents naturally present in different foods, are vitamins E and D, polyunsaturated fatty acids (PUFAs), and selenium, the important biogenic trace element [136][137][138][139][140][141]. Special attention among scientific community is given to investigation and usage of plants as a source of polyphenolic compounds.…”
Section: Pollen As a Source Of Nutraceuticalsmentioning
confidence: 99%
“…Studying of nutraceuticals has increased in last decades due to the significant expansion of cancer all around the world. According to the literature, some of the most important anti-cancer agents naturally present in different foods, are vitamins E and D, polyunsaturated fatty acids (PUFAs), and selenium, the important biogenic trace element [136][137][138][139][140][141]. Special attention among scientific community is given to investigation and usage of plants as a source of polyphenolic compounds.…”
Section: Pollen As a Source Of Nutraceuticalsmentioning
confidence: 99%
“…It also has several advantages in diabetes mellitus and inhibiting tumor cells [28]. It has been already studied that the dietary intake of fish or fish oil can reduce the risk of several types of cancer such as colorectal and prostatic cancers [29]. Nutrition specialists and dieticians suggested that the required ratio of n-6 and n-3 PUFA should be 5:1 or less.…”
Section: Introductionmentioning
confidence: 99%
“…One remarkable feature of these dietary compounds and their metabolic derivatives is the ability to act pleiotropically to prevent the development and progression of cancer [1,2]. Indeed, they have been shown to reduce inflammation and induce its resolution [3], as well as to foster apoptosis [4] and differentiation [5] in cancer cells.…”
Section: Introductionmentioning
confidence: 99%